1989
DOI: 10.1080/00288233.1989.10417922
|View full text |Cite
|
Sign up to set email alerts
|

Forage shrubs in North Island hill country 3. Forage digestibility

Abstract: A range of shrubs was evaluated as potential sources of forage for grazing animals. Shrubs were established in rows in hill pastures near Woodville. Nine"true" shrubs, and two erectgrasses, pampas grass (Cortaderia selloana), and toetoe (C. fulvida) were evaluated. The true shrubs were:Chamaecytisus palmensis, tagasaste: Medicago arborea, tree medic; Ulex europaeus, gorse (two variants: wild gorse and short-spined gorse); Cytisus scoparius, broom; Robinia pseudoacacia, black locust; Leptospermumscoparium, manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In vitro digestibility (80%) and total N content of 33 g N/kg DM (crude protein = 206 g/kg DM) were similar to those estimated by Borens & Poppi (1990). Levels of Na in the foliage harvested from plants at the moist site were lower than recommended (Grace 1983), and were very similar to those found in leaves of the species grown in nearby hill country (Lambert et al 1989c). However this deficiency would probably be overcome in a mixed pasture/ shrub association because of pasture's relatively high Na levels (Table 7).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In vitro digestibility (80%) and total N content of 33 g N/kg DM (crude protein = 206 g/kg DM) were similar to those estimated by Borens & Poppi (1990). Levels of Na in the foliage harvested from plants at the moist site were lower than recommended (Grace 1983), and were very similar to those found in leaves of the species grown in nearby hill country (Lambert et al 1989c). However this deficiency would probably be overcome in a mixed pasture/ shrub association because of pasture's relatively high Na levels (Table 7).…”
Section: Discussionmentioning
confidence: 53%
“…foliage compared favourably with that of the non-N-fixing shrubs (manuka, tauhinu) and erect grasses (pampas, toetoe) evaluated by Lambert et al (1989c, d) in lower North Island hill country. With respect to N content, the willows (17-37 g N/kg DM) were higher than any of the earlier evaluated species (10-12 g N/kg DM; Lambert et al 1989d), whereas in vitro digestibility of S. matsudana x alba Tangoio (65-80%) exceeded that of manuka, pampas, and toetoe (Lambert et al 1989c). Pampas (Cortaderia spp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high preference group was tree medic, short spine gorse, and black locust, the moderate group comprised tagasaste, ceanothus, and broom, and members of the poor group were gorse, manuka, tauhinu, toetoe, and pampas. This ranking relates well to the digestibility of the browse species, with the notable exception of short spine gorse (Lambert et al 1989b), but corresponds more poorly, especially for sheep, with the rankings obtained from a cafeteria-style indoor experiment (Lambert et al 1989a). Lambert et al (1989b) reported the in vivo digestibility of tree medic, tagasaste, and black locust as being in the range 76-81 %; ceanothus and broom 71-73%; short spine gorse, tauhinu, and gorse 63-67%; and manuka, toetoe, and pampas 47^8%.…”
Section: Discussionmentioning
confidence: 99%
“…This ranking relates well to the digestibility of the browse species, with the notable exception of short spine gorse (Lambert et al 1989b), but corresponds more poorly, especially for sheep, with the rankings obtained from a cafeteria-style indoor experiment (Lambert et al 1989a). Lambert et al (1989b) reported the in vivo digestibility of tree medic, tagasaste, and black locust as being in the range 76-81 %; ceanothus and broom 71-73%; short spine gorse, tauhinu, and gorse 63-67%; and manuka, toetoe, and pampas 47^8%. The high preference for short spine gorse by both goats and sheep in our experiment suggested that digestibility was not the only factor affecting its palatability.…”
Section: Discussionmentioning
confidence: 99%